Authors beware! Publishing in predatory journals is harmful - Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2020)
Predatory publishing is now rapidly growing and becoming a global challenge to scientific communities. Predatory publications pose a danger that could undermine the quality, integrity, and reliability of published scientific research works. They harm the career of those authors who published on them. The researchers should be aware of the quality of journals while publishing their research results. In this review, we briefly summarize the ways to spot out predatory publications, their harmful effects, and strategies to stop them. Authors should know the lists of predatory journals/publishers which are available on Beall’s list on the internet. Predatory journals take advantage of authors by asking them to publish for a fee without providing peer-review or editing services. The young and inexperienced authors are easy victims of predatory publications. The predatory publications are worthless, just a waste of time, resources, money, and efforts. The objective of this review paper was to create awareness about predatory journals among researchers and scholars.